Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1007/s00125-019-4849-6
|View full text |Cite
|
Sign up to set email alerts
|

No direct effect of SGLT2 activity on glucagon secretion

Abstract: Aims/hypothesis Sodium-glucose cotransporter (SGLT) 2 inhibitors constitute a new class of glucose-lowering drugs, but they increase glucagon secretion, which may counteract their glucose-lowering effect. Previous studies using static incubation of isolated human islets or the glucagon-secreting cell line α-TC1 suggested that this results from direct inhibition of alpha cell SGLT1/2-activity. The aim of this study was to test whether the effects of SGLT2 on glucagon secretion demonstrated in vitro could be rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
80
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(85 citation statements)
references
References 34 publications
5
80
0
Order By: Relevance
“…SGLT2 inhibition has been suggested to promote endogenous glucose production in response to increased pancreatic secretion of glucagon [41,42], thus potentially masking, or blunting the benefits of SGLT2 inhibition. Our data, consistent with recent reports from animal studies of isolated perfused rat pancreas [43], and human studies describing inter-individual heterogeneity of SGLT2 expression and function in pancreatic islets [44], showed that glucagon concentration was unaffected by SGLT2 inhibition.…”
Section: Discussionsupporting
confidence: 93%
“…SGLT2 inhibition has been suggested to promote endogenous glucose production in response to increased pancreatic secretion of glucagon [41,42], thus potentially masking, or blunting the benefits of SGLT2 inhibition. Our data, consistent with recent reports from animal studies of isolated perfused rat pancreas [43], and human studies describing inter-individual heterogeneity of SGLT2 expression and function in pancreatic islets [44], showed that glucagon concentration was unaffected by SGLT2 inhibition.…”
Section: Discussionsupporting
confidence: 93%
“…Another series of putative annotated metabolites involved in galactose metabolism were differentially abundant. In fact, Arg plays an important role in regulating energy metabolism [56], which can stimulate the release of hormones, such as glucagon, to accelerate the conversion of galactose to glucose [57,58], and then may reduce the synthesis of oligosaccharides. In addition, a negative correlation between the levels of serum oligosaccharides and the abundance of Ruminococcaceae (R = − 0.588, P = 0.035 for raffinose and R = − 0.555, P = 0.040 for stachyose) was also observed.…”
Section: Discussionmentioning
confidence: 99%
“…61 Moreover, some studies have suggested that SGLT2i may exert a direct stimulatory effect on alfa cells, 62,63 although this finding is controversial and has not been consistently replicated in all studies. 64,65 Oxidation of ketone bodies produces more amounts of ATP per molecule of oxygen than glucose or fatty acids oxidation does and may provide a more efficient energy source for the myocardium. 61 In fact, enhanced production of ketone bodies has been proposed as one mechanism driving protection from cardiovascular death and heart failure observed during SGLT2i therapy.…”
Section: Ketone Bodiesmentioning
confidence: 99%